A call to action for health, environment, and development leaders - Tallis, Heather; Merz, Barbara J.; Huang, Cindy; Kreis, Katharine; Olander, Lydia; Ringler, Claudia; Zhang, Wei (Duke University, 2017)
The Bridge Collaborative links experts in the global health, environment, and development fields to tackle one of the largest remaining challenges for cross-sector impact: our fragmented evidence base. We aim to develop an approach that spans across these interdependent sectors to generate a shared evidence base that will inform strategies, shape policies, reduce unintended negative consequences, and direct funding decisions for more sustainable and equitable development.